2003
DOI: 10.1104/pp.103.026716
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of Aconitase Results in an Enhanced Rate of Photosynthesis and Marked Shifts in Carbon Partitioning in Illuminated Leaves of Wild Species Tomato

Abstract: Wild species tomato (Lycopersicon pennellii) plants bearing a genetic lesion in the gene encoding aconitase (Aco-1; aconitate hydratase EC 4.2.1.3) were characterized at molecular and biochemical levels. The genetic basis of this lesion was revealed by cloning the wild-type and mutant alleles. The mutation resulted in lowered expression of the Aco-1 transcript and lowered levels of both cytosolic and mitochondrial aconitase protein and activity. After in silico analysis, we concluded that in the absence of a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
170
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(185 citation statements)
references
References 72 publications
12
170
3
Order By: Relevance
“…It is not the case in Saccharomyces cerevisiae, in which a unique gene encodes both mitochondrial and cytosolic ACOs [38,39]. In plants, several reports indicate that, as in yeast, both mitochondrial and cytosolic ACOs are encoded by the same genes, suggesting a dual targeting of the proteins [40][41][42]. Therefore the question we had to address was whether or not the three identified ACOs were targeted to the cytosol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not the case in Saccharomyces cerevisiae, in which a unique gene encodes both mitochondrial and cytosolic ACOs [38,39]. In plants, several reports indicate that, as in yeast, both mitochondrial and cytosolic ACOs are encoded by the same genes, suggesting a dual targeting of the proteins [40][41][42]. Therefore the question we had to address was whether or not the three identified ACOs were targeted to the cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…The relative contribution of each ACO isoform to the mitochondrial and cytosolic ACO activities, to the metabolism [42], to the regulation of oxidative stress and to the establishment of defence against pathogens [20,45] could be studied with the loss-of-function mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Plants were handled as described in the literature (Carrari et al, 2003;Nunes-Nesi et al, 2005). For the drought stress treatments, well-watered 7-week-old flowering tomato plants were used.…”
Section: Methodsmentioning
confidence: 99%
“…A wide range of mutant, antisense, or silenced plants with deficient expression of enzymes from the TCA cycle have been described, including citrate synthase (Landschü tze et al, 1995), aconitase (Carrari et al, 2003), malate dehydrogenase (Nunes-Nesi et al, 2005), fumarase , succinyl CoA ligase (Studart-Guimarães et al, 2007), and NAD + -dependent isocitrate dehydrogenase (Lemaitre et al, 2007). These studies have shown that modifications in the TCA cycle can modulate photosynthetic performance and, in the case of potato (Solanum tuberosum) citrate synthase, lead to a specific disintegration of the ovary tissues of flower.…”
mentioning
confidence: 99%